Access to 1, 4‐Thiazepanes via Gold‐Catalyzed 7‐exo‐dig Thioallylation and their Cycloisomerization to Bicyclic [4.3.1] Bridgehead‐Olefinic Systems. Issue 18 (25th August 2022) - Choury, Mickael; Wagner, Patrick; Rognan, Charlou; Blond, Gaëlle; Gulea, Mihaela
Abstract: A series of 1, 4‐thiazepanes were synthesized using gold‐catalysis from 1, 3‐aminothioethers having two or three carbon stereocenters. The process consists in a 7‐ exo ‐dig cyclization with C−S bond formation and concomitant allyl S‐to‐C migration, which occurs intramolecularly as demonstrated by a cross‐over experiment. X‐ray crystal‐structure analysis of one product confirmed the expected stereochemistry. Two examples of reactions, azide‐alkyne cycloaddition (CuAAC) and N ‐alkylation, illustrate the potential post‐functionalization of the synthesized 1, 4‐thiazepanes. Finally, the N ‐propargyl 1, 4‐thiazepanes underwent a sulfur‐assisted 1, 6‐enyne cycloisomerization, which led through a 6‐ exo ‐dig cyclization to N, S ‐heterobicyclo[4.3.1] systems with a bridgehead double bond. Abstract :